Effect of exercise and weight loss in polycystic ovarian syndrome among obese women - Cochrane, Thomas; Tengku Kamalden, Tengku Fadilah; Davey, Rachel; Omar Dev, Roxana Dev (Universiti Putra Malaysia, 2021)
Ovulation and fertility can be improved by weight loss in obese women with Polycystic Ovarian Syndrome (PCOS). The aim of this study was to investigate the effectiveness of a twelve-week supervised exercise program in combination with dietary restrictions for obese women with PCOS. The study is a quasi-experimental research and used an experimental pre- and post-test design. Fifteen women recruited from Fertility Clinic, Jessops Hospital for Women, Sheffield took part in this study. Respiratory exchange ratio (RER), heart rate, perceived exertion (RPE), and Houston non-exercise activity code were recorded. Height, weight, and body girth measurements were taken to calculate body mass index, fat percentage, and lean body weight. The intervention group lost an average of 3.1 kg and gained 3.45 kg of lean body weight. Loss of fat percentage was 12.1%. No significant difference was found in the control group. The RER and heart rate value decreased for the same workload in the intervention group, indicating higher tolerance towards exercise intensity. However, the changes for both groups were not significant. The average group compliance rate was 53% (at least two sessions per week). Bearing in mind the small sample size (n=4) for control, the improvement in fitness, significant weight loss, and body composition change (increase in fat-free mass) was achieved in this study. Twelve weeks of exercise, combined with dietary advice, were sufficient to benefit PCOS obese women. The research has achieved a commendable weight-loss objective and has demonstrated increases in standards of fitness among obese women.